The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/ijms232315336
|View full text |Cite
|
Sign up to set email alerts
|

Association of the FCN2 Gene Promoter Region Polymorphisms with Very Low Birthweight in Preterm Neonates

Abstract: Single nucleotide polymorphisms (SNPs) localised to the promoter region of the FCN2 gene are known to influence the concentration of ficolin-2 in human serum and therefore potentially have clinical associations. We investigated the relationships between SNPs at positions −986 (A > G), −602 (G > A), −64 (A > C) and −4 (A > G) and clinical complications in 501 preterms. Major alleles at positions −986 and −64 and A/A homozygosity for both polymorphisms were less frequent among babies with very low bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 39 publications
(48 reference statements)
1
6
0
Order By: Relevance
“…Our data confirmed association of the FCN2 gene promoter polymorphisms and ficolin-2 concentration, published previously by others and ourselves ( 20 , 28 , 52 ). We previously reported also the relationship of 3’UTR diplotypes (group VI) with low ficolin-2 ( 21 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data confirmed association of the FCN2 gene promoter polymorphisms and ficolin-2 concentration, published previously by others and ourselves ( 20 , 28 , 52 ). We previously reported also the relationship of 3’UTR diplotypes (group VI) with low ficolin-2 ( 21 ).…”
Section: Discussionsupporting
confidence: 93%
“…The differences in ficolin-2 levels were analysed in the context of the FCN2 gene promoter haplotype GGCA [corresponding to single nucleotide polymorphisms at positions: -986 (rs3124952); -602 (rs3124953); -64 (rs7865453); -4 (rs17514136)] ( 28 ) and 3’UTR group VI diplotype ( 21 ), both associated with low ficolin-2 concentration.…”
Section: Methodsmentioning
confidence: 99%
“…The GGCA haplotype had the opposite effect, independently of GA. Finally, the AGAG/GGAA diplotype was associated with both shorter (<33 weeks) GA and body mass at birth <1500 g ( 174 ). Earlier, Kilpatrick et al.…”
Section: Clinical Associations Of Ficolins In the Neonatementioning
confidence: 94%
“…Recently, Szala-Poździej et al. ( 174 ) reported associations of SNPs localised to the FCN2 gene promoter with birthweight and/or gestational age in Polish preterm babies. Major alleles for rs3124952 (-986 A>G), rs7865453 (-64 A>C) and A/A homozygosity for both mentioned SNP were found less frequently among newborns with very low birthweight (VLBW, ≤1500 g) compared with the corresponding reference group.…”
Section: Clinical Associations Of Ficolins In the Neonatementioning
confidence: 99%
“…Szala-Poździej et al [ 14 ] reported that some FCN2 gene promoter region polymorphisms that are associated with relatively low serum levels of ficolin-2 significantly increase the risk of very low birthweight in preterm neonates.…”
mentioning
confidence: 99%